3 (x +26)=3.5(X-26)这道方程怎么解
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 02:34:03
3(x+26)=3.5(X-26)这道方程怎么解3(x+26)=3.5(X-26)这道方程怎么解3(x+26)=3.5(X-26)这道方程怎么解3(x+26)=3.5(x-26)3x+3×26=3.5
3 (x +26)=3.5(X-26)这道方程怎么解
3 (x +26)=3.5(X-26)这道方程怎么解
3 (x +26)=3.5(X-26)这道方程怎么解
3(x+26)=3.5(x-26)
3x+3×26=3.5x-3.5×26
3.5x-3x=3×26+3.5×26
0.5x=(3+3.5)×26
0.5x=6.5×26
x=6.5×2×26
x=338
(X-5)(X+3)+(X-2)(X+4)=26
若x^3+x^2+x+1=0,则x^-27+x^-26+x^-25+……+x^-1+1+x+……+x^26+x^27
matlab解决约束非线性规划问题myfun.mfunction f=myfun(x)f=x(1)*x(13)+x(2)*x(14)+x(3)*x(15)+x(25)+1.697*(x(4)*x(16)+...x(5)*x(17)+x(6)*x(18)+x(26))+0.575*(x(7)*x(19)+x(8)*x(20)...+x(9)*x(21)+x(27))+0.723*(x(10)*x(22)+x(11)*x(23)+x(12)*x(24));
matlab解决约束非线性规划问题myfun.mfunction f=myfun(x)f=x(1)*x(13)+x(2)*x(14)+x(3)*x(15)+x(25)+1.697*(x(4)*x(16)+...x(5)*x(17)+x(6)*x(18)+x(26))+0.575*(x(7)*x(19)+x(8)*x(20)...+x(9)*x(21)+x(27))+0.723*(x(10)*x(22)+x(11)*x(23)+x(12)*x(24));
若x^3+x^2+x+1=0,求x^-27+x^-26+...+x^-1+1+x+...+x^26+x^27的值
3X-18=13.2 1.5X-X=6 4X+1.2X=26
(x-25)+(x-23)+(x-27)+(x-21)+(x-26)=x 求x
x=26,X^2-3x+4.21=?
3x+2X(10-x)=26 是
因式分解:x^3+9x^2+26x+24=
x/2+x/3+x/4=26
x/2减x/3减x/4=26
5x-26=3x-10,
5x-26=3x-10
x-3x=26怎么解
3x=26+x怎么解
X+26=3X怎么解,
3x+x+6=26